2015
DOI: 10.1158/0008-5472.can-15-0888
|View full text |Cite|
|
Sign up to set email alerts
|

Combining miR-10b–Targeted Nanotherapy with Low-Dose Doxorubicin Elicits Durable Regressions of Metastatic Breast Cancer

Abstract: The therapeutic promise of microRNA in cancer has yet to be realized. In this study, we identified and therapeutically exploited a new role for miR-10b at the metastatic site, which links its overexpression to tumor cell viability and proliferation. In the protocol developed, we combined a miR-10b-inhibitory nanodrug with low-dose anthracycline to achieve complete durable regressions of metastatic disease in a murine model of metastatic breast cancer. Mechanistic investigations suggested a potent anti-prolifer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 23 publications
9
86
0
Order By: Relevance
“…Recently, DEmiRNAs identified in TNBC have been found to be associated with the aggressive phenotype 14,15 . More importantly, emerging evidences have shown miRNAs could be applied to clinic as diagnostic/ prognostic biomarkers and therapeutic strategies for breast cancer [16][17][18] . Overall, identification of novel biomarkers for TNBC is currently a high priority, and miR-NAs as potential biomarkers, require better understanding of their roles and mechanisms in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DEmiRNAs identified in TNBC have been found to be associated with the aggressive phenotype 14,15 . More importantly, emerging evidences have shown miRNAs could be applied to clinic as diagnostic/ prognostic biomarkers and therapeutic strategies for breast cancer [16][17][18] . Overall, identification of novel biomarkers for TNBC is currently a high priority, and miR-NAs as potential biomarkers, require better understanding of their roles and mechanisms in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miRs can transcriptionally inhibit the expression of target genes by binding to the 3'-untranslated region (3'-UTR), acting as oncogenes or tumor inhibitors (10). A growing number of studies have indicated that abnormal expression of miRs is associated with human breast cancer (11)(12)(13)(14)(15)(16). Furthermore, mounting evidence indicates that miRs serve key functions in the development of TNBC (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, silencing miR-10b expression suppresses cancer cell proliferation, migration, and invasion in vitro as well as tumor growth or metastasis in vivo (14, 18, 19, 22), suggesting that miR-10b is a potential target for anti-tumor or anti-metastatic therapy. Notably, combining nanoparticle-encapsulated miR-10b inhibitors with low-dose doxorubicin achieved complete durable regression of metastases in a xenograft model of breast cancer (23). Intriguingly, miR-10b is secreted by metastatic breast cancer cells via exosomes and, upon uptake, induces invasiveness of non-malignant mammary epithelial cells (24).…”
Section: Introductionmentioning
confidence: 99%